2018
DOI: 10.1021/acs.jproteome.8b00663
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Lipidomics Analyses Reveal Metabolic Reprogramming in Human Glioma with IDH1 Mutation

Abstract: Mutations in isocitrate dehydrogenase (IDH) 1 are high-frequency events in low-grade glioma and secondary glioblastoma, and IDH1 mutant gliomas are vulnerable to interventions. Metabolic reprogramming is a hallmark of cancer. In this study, comprehensive metabolism investigation of clinical IDH1 mutant glioma specimens was performed to explore its specific metabolic reprogramming in real microenvironment. Massive metabolic alterations from glycolysis to lipid metabolism were identified in the IDH1 mutant gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 38 publications
6
82
0
6
Order By: Relevance
“…20,21 In both IDH1 mut glioma tissues and glioma cell culture models with the IDH1 mutation, a decrease in both glutamate and lactate levels is reported. 22,23 These observations confirm our data and support an increased conversion of both lactate and glutamate into glioma cells with the IDH1 mut. A lack of significant changes in abundance of glycolysis enzymes corroborates with our gene expression data and the findings of Lenting and co-workers.…”
Section: Discussionsupporting
confidence: 89%
“…20,21 In both IDH1 mut glioma tissues and glioma cell culture models with the IDH1 mutation, a decrease in both glutamate and lactate levels is reported. 22,23 These observations confirm our data and support an increased conversion of both lactate and glutamate into glioma cells with the IDH1 mut. A lack of significant changes in abundance of glycolysis enzymes corroborates with our gene expression data and the findings of Lenting and co-workers.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent work, Zhou et al () analysed the metabolome and the lipidome of 75 human glioma samples, 30 of which contained R132H IDH1 mutations. They found that: ( i ) glycolytic intermediates were significantly decreased in glioma tissues with IDH1 mutation compared to samples bearing the wild‐type IDH1 gene; ( ii ) TCA cycle intermediates were not affected, with the exception of 2‐ketoglutarate and isocitric acid whose levels were reduced; ( iii ) levels of glutamine and glutamate were similar in the two types of glioma tissues; ( iv ) lipid metabolism was extensively altered in the IDH1‐mutant glioma tissues.…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…They found that: ( i ) glycolytic intermediates were significantly decreased in glioma tissues with IDH1 mutation compared to samples bearing the wild‐type IDH1 gene; ( ii ) TCA cycle intermediates were not affected, with the exception of 2‐ketoglutarate and isocitric acid whose levels were reduced; ( iii ) levels of glutamine and glutamate were similar in the two types of glioma tissues; ( iv ) lipid metabolism was extensively altered in the IDH1‐mutant glioma tissues. In particular, a marked decrease of triglycerides and of sphingolipids was observed in mutant compared to wild‐type tissues and was associated with the lower expression of long‐chain acyl‐CoA synthetase 1 and 4 (ACSL1 and 4) and of very long‐chain acyl‐CoA synthetase 3 (ACSVL3) detected in IDH1‐mutant gliomas (Zhou et al , ). Other recent studies have reported remarkable alterations in the phospholipid composition of IDH‐mutant versus IDH‐wild‐type glioma patient‐derived xenografts (Fack et al , ).…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…Since the original studies describing IDH1 mut and its neoenzymatic activity in cancer, a great deal of research has been done studying the metabolic effects of IDH1 mut , often generating conflicting results. For example, whereas some have shown that IDH1 mut depletes the cell of TCA intermediates [19-24], others have found little to no change [10, 25, 26], and that IDH1 mut gliomas may use lactate and glutamate anaplerosis to replenish TCA intermediates [27]. Some have suggested that glycolysis is reduced in IDH1 mut gliomas [21, 25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, whereas some have shown that IDH1 mut depletes the cell of TCA intermediates [19-24], others have found little to no change [10, 25, 26], and that IDH1 mut gliomas may use lactate and glutamate anaplerosis to replenish TCA intermediates [27]. Some have suggested that glycolysis is reduced in IDH1 mut gliomas [21, 25]. However, one group found reduced glucose uptake by IDH1 mut glioma cells, but otherwise no difference in the rate of glycolysis compared to IDH1 wt cells [26].…”
Section: Discussionmentioning
confidence: 99%